2008
DOI: 10.1007/s10661-008-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of waterscape beauties through visual quality assessment method

Abstract: Besides being an indispensable life element, water is also in the first rows among the most important landscape elements that have the visual reserve value in both natural and cultural environments. In this study, the aim was to present suggestions about the use of waterscapes in landscape design and planning attempts by determining the water types bearing high visual reserve values among different types of waterscapes bearing high visual reserve values. The visual quality assessment method was used in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 36 publications
1
38
0
1
Order By: Relevance
“…It is also worth mentioning that this article compared the two data sources based on a population aged [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. This group constitutes the major users of social media in China.…”
Section: A Combined Evaluation Methodsmentioning
confidence: 99%
“…It is also worth mentioning that this article compared the two data sources based on a population aged [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. This group constitutes the major users of social media in China.…”
Section: A Combined Evaluation Methodsmentioning
confidence: 99%
“…The visual landscape is an important part of humanity's everyday life experience (Bulut and Yilmaz, 2009). Visual preference for landscapes has received a lot of attention for the past half century and a number of theories explaining landscape *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Water is one of the most indispensable elements in different landscapes; it has a visual reverse value in scenery and provides users with recreational opportunities [1]. Landscapes with large water bodies (i.e., oceans) tend to be among the most preferred landscapes [2], and water bodies are in fact also positive factors in landscape perception [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ryan [18], Pfluger et al [19], and Vesterinen et al [20] have shown that water clarity is an important determinant of public perception of water quality. A water surface with a good visual quality can attract more tourists [1] [21] and the visual satisfaction of people observing a water body is thus very important.…”
Section: Introductionmentioning
confidence: 99%